UPAYA MENINGKATKAN MOTIVASI SISWA DENGAN MENGGUNAKAN MEDIA VISUAL PADA MATERI MENGGAMBAR ILUSTRASI DI KELAS VIII SMPN 3 BATANGHARI - Erdiani Erdiani (Dharmas Education Journal (DE_Journal), 2020)
The problem in this research is that there are still many students who get difficulty in making illustration images, most students think that drawing illustrations is a difficult thing, because they have to think of a form of image that can emphasize what is described in the writing or story, because of that many students are less interested, and less active in participating in the learning process. This of course can reduce student motivation to learn illustration drawing techniques. This research is a classroom action research (CAR) which aims to increase student motivation by using visual media in drawing illustration materials in class VIII SMPN 3 Batanghari. This research was conducted in September-December 2018. The study consisted of 2 cycles, each cycle going through the stages of planning, implementing action, observing, and reflecting. The techniques used to collect data were filling out questionnaires, interviews and observations. From the data analysis, it is known that there is an increase in student motivation by using visual media in the illustration drawing material. The increase in the score of teacher and student activity from cycle I to cycle II is from 72.5% to 81.25%. Student activity also increased from 71.43% to 82.14%.